English as a lingua franca in teacher education a Brazilian perspective - Gimenez, Telma; El Kadri, Michelle Salles; Simões Calvo, Luciana Cabrini (Developments in English as a lingua franca ;, 2018)
A lingua franca perspective into English language teaching in Brazil has only recently take flight. As an emerging economy, the country faces enormous challenges when it comes to language education in schools, where English has traditionally been taught as a foreign language. This collection brings the perspectives of academics and language practitioners in their efforts to incorporate an ELF approach into teacher education, thus offering a voice sorely missed in the international community interested in developing new approaches to English in a global world.